GAMBARAN PENGETAHUAN, SIKAP, DAN PERILAKU REMAJA TENTANG ARAK OPLOSAN DI SMK X KABUPATEN KARANGASEM - Noviantari, Ni Nyoman Windy; Suindrayasa, I Made; Suarningsih, Ni Kadek Ayu (Coping: Community of Publishing in Nursing; Vol 12 No 4 (2024): Agustus 2024DO - 10.24843/coping.2024.v12.i04.p12, 2025)
Balinese wine is one of the traditional alcoholic drinks from Indonesia. Balinese wine contains ethanol, but in its traffic Balinese wine is mixed with other ingredients and turn into wine that contain methanol or called blended Balinese wine. Adolescent are one of the most potential consumers of blended Balinese wine. This study aimed to describe the knowledge, attitudes, and behavior about blended Balinese wine among adolescent at Vocational High School X Karangasem. This research was a descriptive quantitative study with cross sectional design. Proportionate stratified random sampling was use to recruit 234 respondents. Data analysis was showed by univariate analysis. The result of this study showed majority of respondents had good knowledge (66.7%), 23.5% respondents had sufficient knowledge, and 9.8% respondents had poor knowledge. Meanwhile, respondents who had positive attitude were 51.3% and respondents who had negative attitude were 48.7%. 73.1% respondents had good behavior, but 26.9% respondents had poor behavior towards the consumption of blended Balinese wine. The conclusion of this study was most of respondents had good knowledge and behavior and also positive attitudes. On the other hands, there were respondents who had poor knowledge and behavior and also negative attitude towards the consumption of blended Balinese wine. Both the school and health workers are advised to provide education or outreach about blended balinese wine to adolescents as an effort to prevent and control the behavior of adolescents who consume blended balinese wine.